Stories from a migrant city Living and working together in the shadow of Brexit - Rogaly, Ben (Book collections on Project MUSE., 2020)
Taking a biographical approach, the book explores the causes and consequences of moving or staying put in the context of class inequality and racisms, and looks for commonalities between people often seen as irredeemably divided.